2012
DOI: 10.1002/star.201200198
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation and stability of starch under different processing conditions

Abstract: The objectives of this paper are to review the thermal degradation and stability of starch and starch‐based materials, including both fundamental sciences such as detecting techniques, the effect of amylose/amylopectin content in starches and starches modifications, as well as the effect of different processing environments, such as an open or sealed system, and shearless or shear stress conditions. The decomposition temperature of starches was increased with increasing amylopectin content in an open system. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(163 citation statements)
references
References 93 publications
10
145
1
3
Order By: Relevance
“…The type of the emitted gaseous decomposition products indicates mainly on the breaking of the glycosidic bonds, strong bonds and thermal dehydration of starch from studied copolymers under the first decomposition stage. Those observations are in accordance with the results obtained by other researches [28,40,[44][45][46][47][48].…”
Section: Thermal Properties Of Copolymerssupporting
confidence: 93%
“…The type of the emitted gaseous decomposition products indicates mainly on the breaking of the glycosidic bonds, strong bonds and thermal dehydration of starch from studied copolymers under the first decomposition stage. Those observations are in accordance with the results obtained by other researches [28,40,[44][45][46][47][48].…”
Section: Thermal Properties Of Copolymerssupporting
confidence: 93%
“…The results showed that the starch extrudate particles were found to be more thermally stable than native corn starch. The emulsifier was a coupling agent that improved the compatibility between the hydroxyl of starch and the ester bond of emulsifiers and then the thermal stability of starch extrudate particles improved (Liu et al 2013;Tupa et al 2015). The results clearly illustrated that the emulsifier significantly enhanced the thermal stability during extrusion processing.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 89%
“…Low SME at high moisture content (Figure 2) could be explained by the decrease of shearing, attributed to the lubricating effect of water by reducing the total molecular weight in the mixer, whereas an increase of SME with increase of rpm is due to the molecular friction caused by the simultaneous increase in shear rate [18] . and 70.0 °C, respectively.…”
Section: Functional Propertiesmentioning
confidence: 99%